Analisis Faktor-Faktor Yang Mempengaruhi Profitabiltas Bank Umum Syariah di Indonesia - Ria, Nuriatullah (Jeksyah: Islamic Economics Journal, 2022)
This research was aimed to know and analyze the influence of FDR, CAR, BOPO, BI Rate, and Inflation  toward the profitability which is measured by using ROA at the Islamic Commercial Bank in Indonesia. The population of this research was all of Islamic Commercial Bank in Indonesia. The sample was purposive sampling which take years of research from 2017 up to 2021 by using secondary data. The test showed that FDR has positive and insignificant to the profitability (ROA) at Islamic Commercial Bank in Indonesia. Meanwhile CAR and BOPO variable has negative and significant to the profitability (ROA) at Islamic Commercial Bank in Indonesia, external Bank variable which was BI rate and inflation has positive influence and insignificant to the profitability (ROA) at Islamic Commercial Bank in Indonesia. The result of coefficient correlation test (R2) dependent variable with independent variable was 0,834914 or 83,48%. It shows that dependent ROA variable and independent variable (FDR, CAR, BOPO, BI RATE, inflation) has pretty strong relationship 83,48%. More over the other percentage 16,52% was influenced by other variables which did not include in this research.